A Second Look at Credit Crunch: The Philippine Case - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 1999)
This paper tries to verify empirically the claim that there has been a credit crunch in the Philippines since the onset of the Asian financial crisis in July 1997. The results of the analysis using both macro and micro level data do not support such claim. Instead, the results tend to show that the current slowdown in bank loans is merely a reflection of the economic downturn. The paper recommends that policymakers focus their attention on raising aggregate demand using both monetary and fiscal policies.
Keywords: 330; Asian financial crisis